2019
DOI: 10.1177/1558925019861239
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of three-dimensional near-net-shape weave structures for high technical performance in carbon fibre–reinforced plastics

Abstract: To tap the full potential of reinforcing fibres for lightweight construction of sustainable carbon fibre–reinforced plastic components, woven three-dimensional reinforcement structures open up innovative approaches by integrating functional features. In this work, a novel three-dimensional shuttle weaving technology was taken advantage of to study carbon reinforcement structures with uninterrupted load trajectories from three points of view. Mechanical principals, economic and environmental issues were focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The cross-industry applications of fiber-reinforced composites for structural components with profile, planar, or shell shapes have been described in the literature. [1][2][3][4][5] The manufacturing process of coreless filament winding (CFW) 6,7 allows its utilization in shells 8 and lattice frameworks. 9 For technical applications where high specific mechanical properties are required, CFW offers a superior performance, since it allows for full control over the component geometry and fiber orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-industry applications of fiber-reinforced composites for structural components with profile, planar, or shell shapes have been described in the literature. [1][2][3][4][5] The manufacturing process of coreless filament winding (CFW) 6,7 allows its utilization in shells 8 and lattice frameworks. 9 For technical applications where high specific mechanical properties are required, CFW offers a superior performance, since it allows for full control over the component geometry and fiber orientation.…”
Section: Introductionmentioning
confidence: 99%
“…10 The weaving method can provide high fiber volume fraction and strength, while it cannot manufacture flexible structures at the connection region. 11 The three-dimensional (3-D) braiding method has the advantages of the knitting and weaving method, and could be used to produce multiway tubes with both high strength/weight ratio and seamless uniform structure. For example, Wu et al, 12 Gideon et al, 13 and Yang et al 14 demonstrated that the 3-D braided composite tube has excellent energy absorption capability and the interlacing point could effectively prevent yarns separating from the braided structure.…”
mentioning
confidence: 99%
“…The applied initial warp tension is the most important technological parameter, because the initial warp tension is the key to controlling the yarn hanging and yarn wear in the multi-layer weaving process. 4,5…”
mentioning
confidence: 99%
“…The applied initial warp tension is the most important technological parameter, because the initial warp tension is the key to controlling the yarn hanging and yarn wear in the multi-layer weaving process. 4,5 The warp tension determines the shedding shape and the breakage rate of warp yarns. Warp yarns with low tension or high tension lead to defects during the weaving process, especially in multi-layer weaving processes with a large number of warp yarns.…”
mentioning
confidence: 99%